2015
DOI: 10.1111/jfr3.12224
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity of flood damage estimation to spatial resolution

Abstract: Flood damage estimation is an important element in flood risk assessment; it is useful for mobilizing investment and developing policies for flood loss prevention since most flood risk reduction measures are based on cost benefit analysis. From a global or regional view‐point, it is necessary to understand relative impacts on economies of countries to mobilize international support and develop response strategies. This requires a unified approach to flood damage estimation across countries and over large spati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 21 publications
0
16
0
Order By: Relevance
“…Saksena and Merwade () resampled high‐resolution LiDAR DEMs to DEMs of lower resolution and found a relationship between errors arising from DEM properties to fluvial flood inundation maps. Komolafe et al () investigated the sensitivity of spatial resolution of the flood inundation map to damage estimation and concluded that the underestimation or overestimation of damage is dependent on the data integration approach. They did not take the DEM resolution effects into account and only resampled the 50‐m inundation map obtained in previous studies to coarser resolutions.…”
Section: Introductionmentioning
confidence: 99%
“…Saksena and Merwade () resampled high‐resolution LiDAR DEMs to DEMs of lower resolution and found a relationship between errors arising from DEM properties to fluvial flood inundation maps. Komolafe et al () investigated the sensitivity of spatial resolution of the flood inundation map to damage estimation and concluded that the underestimation or overestimation of damage is dependent on the data integration approach. They did not take the DEM resolution effects into account and only resampled the 50‐m inundation map obtained in previous studies to coarser resolutions.…”
Section: Introductionmentioning
confidence: 99%
“…In summary, the loss differences reached 7.8% and 11.2% during two events when compared with the 1-m and 10-m resolutions. Spatial resolutions used in the assessment had a direct impact on the potential flood heights [21]. However, the flood loss evaluation was often restricted due to the lack of dense observation data [22].…”
Section: Flood Loss Comparison Using Different Resolutionsmentioning
confidence: 99%
“…Elevation errors are thus transferred first to a hydrodynamic model in terms of flood depth errors, and then to damage model errors (Koivumäki et al, 2010). Differences in simulated flood depths are also observed for different DTMs resolutions and sources (Bhuyian & Kalyanapu, 2017;Komolafe, Herath, & Avtar, 2015;Krebs, Kokkonen, Valtanen, Setälä, & Koivusalo, 2014;Sanders, 2007).…”
Section: Introductionmentioning
confidence: 99%